Nutrition adequacy, gastrointestinal, and hepatic function during extracorporeal membrane oxygenation in critically ill adults: A retrospective observational study. Issue 9 (1st May 2022) - Visvalingam, Rozanne; Ridley, Emma; Barnett, Adrian; Rahman, Tony; Fraser, John F.
Abstract: Aims: To identify clinical and biochemical markers associated with nutrition adequacy and gastrointestinal and liver dysfunction in adults on extracorporeal membrane oxygenation (ECMO). Methods: A retrospective, observational, study was conducted at 2 centres in Australia. Adult patients who received ECMO from July 2011 to June 2015 were included. Mode of ECMO used, fluid balance, number of systemic inflammatory response syndrome (SIRS) criteria present, vasoactive‐inotropic scores (VIS) and liver function tests (LFTs) were collected for the duration of ECMO until 7 days after ECMO cessation. Multiple regression models were used to determine if the collected variables were associated with nutrition adequacy. The mean LFTs during ECMO were also compared to mean LFTs post ECMO cessation. Results: During the first 5 days of ECMO commencement, mean nutrition adequacy was 10% higher in the veno‐venous (VV) ECMO group than in the veno‐arterial (VA) group (95% confidence interval [CI], 2% to 17%). For every 5000 ml increase of fluid balance, an associated decrease in nutrition adequacy was observed (−8%, 95% CI: −15% to −2%). A doubling of bilirubin and VIS were associated with a mean reduction in nutrition adequacy of −5% (95% CI –8% to −2%) and − 2% (95% CI: −3% to −1%), respectively. Conclusions: In the first 5 days of ECMO commencement, higher nutrition adequacy was associated with the VV mode of ECMO and reduced nutrition adequacy with increased fluid balance, more vasopressor and inotropic support and raised bilirubin. Prospective investigation is required to confirm whether these associations have a causal relationship. Abstract : This is a large, multicentre, retrospective observational study, which included 176 patients. During the first 5 days of ECMO commencement, decreased nutrition adequacy was associated with a positive fluid balance of 5, 000 ml, a doubling of vasoactive or inotrope support and a doubling of bilirubin. The venoarterial (VA) mode of ECMO was also associated with poorer nutrition (see Figure 1).